Creating an Environment to Educate about the Environment - SINGH, KULDEEP (SCHOOL SCIENCE, 2007)
THE NEW PARADIGM of education, embodying the spirit of science, of democracy, and of care for the environment, emphasises a number of key elements such as learning rather than teaching, building capacity for critical thinking and problem solving along with locale-specificity in the context of a global education (NCF 2005). In the march of science, anybody is welcome to challenge any assertion, whether it be of facts supposedly observed, or of models of how the system works. Along with rejection of all authority, science has also given up claims arriving at any absolute Truth. Science deals in knowledge that is always treated as provisional, that is, open to being supplanted by newer and more effective observations and theories.